2018
DOI: 10.3389/fenvs.2018.00038
|View full text |Cite
|
Sign up to set email alerts
|

Blurred Lines: The Ethics and Policy of Greenhouse Gas Removal at Scale

Abstract: The topic of Greenhouse Gas Removal (GGR) for climate geoengineering is becoming increasingly salient following the IPCC's 5th Assessment Report and the Paris Agreement. GGR is thought of as a separate category to mitigation techniques such as low-carbon supply or demand reduction, yet multiple social, ethical and acceptability concerns cut across categories. We propose moving beyond classifying climate strategies as a set of discrete categories (which may implicitly homogenize diverse technologies), toward a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 53 publications
0
38
0
Order By: Relevance
“…Others, however, make the case for separating BECCS (and other CDR approaches) from a geoengineering 'climate recovery' framing, arguing that it is better identified as an 'emission offsetting' strategy [55] to complement mitigation in a way that is comparable to existing 'enhancement of sinks' policies [56] and consistent with a view of CDR as SRM's less-risky cousin [57•]. This conceptual distinction becomes important, not just for how CDR can be incorporated into policy frameworks [56] but also when considering the ethical and governance implications [58] and, consequently, how it is perceived by different actors [25,58]. This distinction is, in part, predicated on whether CDR is used to enable deeper emission cuts in the near term or to allow an 'overshoot' in carbon budgets.…”
Section: Extending Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Others, however, make the case for separating BECCS (and other CDR approaches) from a geoengineering 'climate recovery' framing, arguing that it is better identified as an 'emission offsetting' strategy [55] to complement mitigation in a way that is comparable to existing 'enhancement of sinks' policies [56] and consistent with a view of CDR as SRM's less-risky cousin [57•]. This conceptual distinction becomes important, not just for how CDR can be incorporated into policy frameworks [56] but also when considering the ethical and governance implications [58] and, consequently, how it is perceived by different actors [25,58]. This distinction is, in part, predicated on whether CDR is used to enable deeper emission cuts in the near term or to allow an 'overshoot' in carbon budgets.…”
Section: Extending Mitigationmentioning
confidence: 99%
“…The literature in this area calls for a more democratic process, one which opens up critical discussion of wider implications, differentiating by scale rather than 'technology', to consider social, ethical, and political impacts of different levels of deployment and decision making (for example, 58,59). Ethical mapping of CCS has identified justice, prevention of harm, and technoscientific and regulatory competence as potential faultlines or areas of contention [71][72][73].…”
Section: Beccs Ccs and Ethicsmentioning
confidence: 99%
“…For these reasons, Dale Jamieson (2013) argues that geoengineering 'does not mark a specific category of response to climate change but simply alerts us to the fact that the approach under discussion is viewed by the speaker as novel, weird, exotic, unfamiliar, or untested' (529). There is also increasing recognition that the issues faced by GGR may in fact be quite different from those faced by SRM and that the two should therefore be disentangled (Cox et al 2018;Heyward 2013). Different approaches may also entail different forms of sociotechnical governance.…”
Section: Stakeholder Discourses On Geoengineering Ggr and Climate Chmentioning
confidence: 99%
“…Research has also identified multiple ethical concerns associated with GGR, which means that deploying it at scale to meet emissions targets is not a foregone conclusion (Cox et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation